Assessment of Emotional Distress Among Hepatitis C Patients Undergoing Antiviral Therapy - Gill, Samerna Aftab; Bashir, Safia; Imtiaz, Mubashira; Tasneem, Syeda Sidra; Jabeen, Rubina (Biological and Clinical Sciences Research Journal, 2025)
Hepatitis C virus (HCV) infection is a major global health concern with significant physical and psychological implications. In Pakistan, where HCV prevalence is among the highest in the world, limited attention is paid to the emotional distress and self-efficacy of patients undergoing antiviral therapy. Psychological distress may hinder treatment adherence and adversely impact health outcomes. Objective: To assess the prevalence of emotional distress and levels of self-efficacy among patients with Hepatitis C undergoing antiviral therapy at a tertiary care hospital in Pakistan. Methods: This descriptive cross-sectional study was conducted over three months (January–March 2024) at a Tertiary care hospital in Lahore. A total of 117 adult patients diagnosed with Hepatitis C and receiving antiviral treatment were recruited using convenience sampling. Data were collected through a structured, pre-validated, Urdu-translated questionnaire that consisted of demographic variables, emotional distress (adapted from the Hospital Anxiety and Depression Scale, HADS), and self-efficacy items (based on the General Self-Efficacy Scale, GSES). Descriptive statistics and inferential tests (Chi-square, t-test, Mann–Whitney U) were performed using SPSS version 26. A p-value of <0.05 was considered statistically significant. Results: Of the 117 patients, 51.3% were female, and the majority (43.6%) were aged between 31 and 35 years. A high prevalence of emotional distress was observed, with 47.0% of participants reporting frequent anxiety and 41.9% experiencing persistent worrying thoughts. Fear and loss of enjoyment were also commonly reported. Self-efficacy was notably low; 46.2% of patients were not at all confident in discussing their illness with a physician, and only 3.4% consistently managed physical discomfort effectively. Emotional distress was more prevalent in female participants, whereas younger patients demonstrated relatively higher self-efficacy. Conclusion: Hepatitis C patients in Pakistan exhibit considerable emotional distress and poor self-efficacy during antiviral therapy. These findings underscore the pressing need for integrated psychosocial interventions, enhanced patient-provider communication, and culturally tailored education programs to promote psychological resilience and treatment adherence.